2017
DOI: 10.1177/1359105317696139
|View full text |Cite
|
Sign up to set email alerts
|

Patients with limited communication in end-of-life situations: Initial psychometric properties of a discomfort observation scale

Abstract: This work presents an observational scale which takes into account different observable indicators of discomfort of patients in end-of-life situations with difficulties in communicating due to cognitive impairment, fatigue or sedation and provides details of its validation. In all, 71 adults participated. Model fit was adequate ( χ(27) = 43.28, p = .024, comparative fit index = .975, root mean square error of approximation = .092 and confidence interval 90% (.033-.140)). Alpha coefficient was .70 and composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Discomfort Observation Scale (DOS) ( Soto-Rubio A.L. et al, 2017 ): this scale was used to assess the emotional state (ESP) in patients with significant cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discomfort Observation Scale (DOS) ( Soto-Rubio A.L. et al, 2017 ): this scale was used to assess the emotional state (ESP) in patients with significant cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
“…The accurate assessment of needs is of capital importance in order to fulfill one of the main objectives of palliative care: the reduction of suffering of patients and their families ( Sepúlveda et al, 2002 ). These needs have been considerably studied in the last 20 years, and based on these studies specific assessment instruments have been developed ( Davis et al, 2016 ; Soto-Rubio A.L. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated a large variation of clinical evaluation methodologies to monitor the clinical efficacy of palliative sedation [ 9 , 10 ]. Additionally, close monitoring of discomfort during palliative sedation is rare [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Symptom management and comfort care, for example, become challenging when patients are unable to communicate verbally. 10 The prevalence and inadequate treatment of symptoms are high among those with cognitive impairments even when receiving palliative care. 11 Several reviews have identified that despite advancements in palliative care for patients with dementia, patients who are unable to make decisions endure poorly managed end-of-life symptom burden and suffering.…”
Section: Introductionmentioning
confidence: 99%